Effect of root canal filling material and level of surgical injury on periodontal healing in dogs - Holland, Roberto [UNESP]; Otoboni Filho, José Arlindo [UENSP]; Bernabé, Pedro Felício Estrada [UNESP]; Souza, Valdir de [UNESP]; Nery, Mauro Juvenal [UNESP]; Dezan Junior, Eloi [UNESP] (Munksgaard Int Publ Ltd, 1998)
Some divergencies in the literature about periodontal healing after surgical injury stimulated the development of this experiment. The root canals of dogs' teeth were negotiated and filled by the lateral condensation technique with two kinds of sealers: Sealapex and zinc oxide-eugenol cement. In the second session, the bone tissue was exposed and one cavity was made at the apical third of the root and another at the border between the coronal and middle thirds, both penetrating into the root canal. Six months later the animals were sacrificed and the specimens prepared for histopathologic analysis. The results showed that the kind of filling material and the level of the periodontal wound exposing the root canal can influence the healing process (P<0.01).
Keywords: periodontal healing; root canal treatment; surgical injury